REDUCTION OF RURAL POVERTY THROUGH SERICULTURE IN SPECIAL REFRENCE OF RURAL WOMEN - Jadhav, Neeta; Yadav, Ulka; Yadav, Nishchhal (International Journal of Research -GRANTHAALAYAH, 2015)
The contribution of rural women in sericulture in since ages, particularly in some of the critical areas is more of result of her innate attachment with the process of producing the best-the Queen of Textiles- and had been unarguably more than a cliché. We ought to learn from the past experiences that suggest devising a frame work of equitable and sustainable development of her participation on a consistent basis. Keeping in view the involvement of rural women in sericulture and silk industry, their present status in society and need for their empowerment, strategies to be incorporated in the various developmental initiatives are suggested.